2022
DOI: 10.1007/s10803-021-05263-7
|View full text |Cite
|
Sign up to set email alerts
|

Parent Activation Measure for Developmental Disabilities (PAM-DD) in Caregivers of Individuals With ASD

Abstract: Activation refers to patients’ belief, knowledge, ability, and persistence to manage care. The concept is adapted to parent activation in developmental disorders. This study examined the psychometrics of the Parent Activation Measure for Developmental Disabilities (PAM-DD) and factors related to parent activation in ASD. Data from 658 caregivers of children with ASD in the Autism Treatment Network Registry Call Back Assessment study were analyzed. The actual ordering of the scale items was inconsistent with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
1
6
2
Order By: Relevance
“…Recent studies have shown that ADHD in children often affect parent-child interactions negatively and that parents of children with ADHD present with higher levels of stress and irrational beliefs related to emotion-focused strategies [47,48]. Compared to other paediatric studies by Pennarola, DeCamp, Liberman and Yu [12,[14][15][16], we found higher activation scores for parents than what have previously been reported. The authors from a study of parent activation in a sample of caregivers of children in an emergency department [15] reported a mean activation score of 73 (SD = 15.74), while Yu et al [16] reported a mean activation score of 67.36 (SD = 5.82) in a sample of caregivers of children with autism spectrum disorders.…”
Section: Relevance To Clinical Practicecontrasting
confidence: 81%
See 4 more Smart Citations
“…Recent studies have shown that ADHD in children often affect parent-child interactions negatively and that parents of children with ADHD present with higher levels of stress and irrational beliefs related to emotion-focused strategies [47,48]. Compared to other paediatric studies by Pennarola, DeCamp, Liberman and Yu [12,[14][15][16], we found higher activation scores for parents than what have previously been reported. The authors from a study of parent activation in a sample of caregivers of children in an emergency department [15] reported a mean activation score of 73 (SD = 15.74), while Yu et al [16] reported a mean activation score of 67.36 (SD = 5.82) in a sample of caregivers of children with autism spectrum disorders.…”
Section: Relevance To Clinical Practicecontrasting
confidence: 81%
“…The exploratory factor analysis in our study suggests an extraction of two factors and demonstrates a strong positive correlation between the factors. Similar to our findings, factor analyses in previous studies have uncovered that the data did not fit the theoretical four-factor model of parent activation and the theoretical structure of patient activation as four factors (beliefs, confidence, action, perseverance) [14][15][16].…”
Section: Factor Structuresupporting
confidence: 76%
See 3 more Smart Citations